PENGARUH MEDIA CIRCLE NUMBER TERHADAP KEMAMPUAN MENGENAL KONSEP BILANGAN PADA ANAK USIA 5-6 TAHUN DI TK NEGERI PEMBINA KINALI KECAMATAN KINALI KABUPATEN PASAMAN BARAT - Gusti Emiliya Sari; Enda Puspitasari; Yeni Solfiah (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2022)
This article reports the study about the effect of the Circle Number media on the ability to recognize the concept of numbers for children aged 5-6 years at Kindergarten of Pembina Kinali. The study described in this article used a quantitative research method in the form of an experiment with a research model of one group pretest-posttest design. Subject of the study involved 15 children in class B, which consisted of nine male children and six female children. The object of the study was the skill to recognize the concept of numbers for children aged 5-6 years. Data collection techniques were collected through observation and documentation. The instrument used was an observation sheet. The test was used as a data collection technique, the data obtained were then processed by using a t-test to see the comparison of pre-test and post-test. Based on the results of the study, the pre-test value was smaller than the post-test value. And with the N-Gain value, it was categorized as a medium category. Hence, it could be concluded that the use of Circle Number media has an effect on the skill to recognize the concept of numbers for children aged 5-6 years.